The Spiral Staircase : My Climb Out of Darkness - Armstrong, Karen (London Harper Perennial, 2005)
The moving story of her own search for God by the highly-acclaimed author of the bestselling A History of God: The 4,000-Year Quest of Judaism, Christianity and Islam; The Battle for God: A History of Fundamentalism; and Islam: A Short History. In 1969, after seven years as a Roman Catholic nun-hoping, but ultimately failing, to find God-Armstrong left her convent. She knew almost nothing of the changed world she was entering, and she was tormented by panic attacks and inexplicable seizures. Her struggle against despair was fueled by a string of discouragements-failed spirituality, doctorate and jobs, fruitless dealings with psychiatrists-but finally, in 1976, she was diagnosed with epilepsy and given proper treatment. She then began the writing career that would become her true calling, and as she focused on the sacred texts of Judaism, Christianity and Islam, her own true inner story began to emerge. She would come to experience brief moments of transcendence through her work-the profound fulfillment that she had not found in the long hours of prayer as a young nun. Powerfully engaging, often heart-breaking, but lit with bursts of humour, The Spiral Staircase is an extraordinary history of self. From the Hardcover edition.
Keywords: Ex-nuns -- Great Britain -- Christian biography